C.02 Delayed new-onset hormone dysfunction following complete and incomplete resection of nonfunctioning pituitary adenomas. (2nd June 2017) - Han, J; Hebb, AL; Imran, SA; Clarke, DB
Abstract : Background: Post-operative delayed hormone dysfunction (DHD) in patients with nonfunctioning pituitary adenomas (NFPA) is highly variable and is predicted based on limited evidence. This study was undertaken to assess the likelihood of developing new DHD and its relation to the extent of tumor resection and recurrence.Methods: Four hundred fifty-five prospectively collected patient files were reviewed from our Program's database. Inclusion criteria: NFPA; underwent surgery; and minimum follow-up of two years. Tumor recurrence was correlated with DHD (starting one year post-operatively) based on standardized annual imaging and hormone testing.Results: Eighty-nine patients met our inclusion criteria: 39 males and 50 females; mean follow-up was 4.3yrs (ranging from 2 to 11yrs). With no post-op residual tumor, the probability of developing DHD was only 7% by six years; no patient in this group developed DHD after three years of follow-up. In contrast, by six years, the probability of DHD was 33% in patients with residual stable tumor, and 54% in those with tumor recurrence/growth.Conclusions: By six years, approximately one third of patients with incomplete resection, and over half with tumor regrowth, will likely develop DHD. In contrast, the risk of DHD with complete tumor resection is <10% and, when seen, occurs within three years of surgery.